Determinants of burnout syndrome among undergraduate nursing students in Poland: a cross-sectional study - Katarzyna Szwamel; Wiesława Kowalska; Ewa Mazur; Anna Janus; Iwona Bonikowska; Justyna Jasik-Pyzdrowska (BMC Medical Education)
Abstract Background Nursing students worldwide are exposed to burnout syndrome resulting from constant academic and clinical stressors. The consequences of student burnout can be related to the student’s mental and physical health. Burnout may affect the learning process, achieving professional skills, and future effectiveness while working with a patient and, eventually, might lead to the decision to quit the job. This study aims to analyze the intensity of burnout syndrome among undergraduate nursing students based on their year of study (1), establishing the impact of stress, anxiety, insomnia, and selected sociodemographic variables on the level of burnout (2) and establishing a student profile predestined to be affected by burnout (3). Methods A cross-sectional study was conducted among 841 bachelor’s degree nursing students from March 2022 to June 2022. The Maslach Burnout Inventory, Athens Insomnia Scale, Modified Hospital Anxiety and Depression Scale, and Perceived Stress Scale were used. Results High levels of emotional exhaustion were found in 40.9% and depersonalization in 20.33%, while low personal accomplishment was found in 16.88% of the students. Students of nursing in Year 2 presented the highest levels of emotional exhaustion and depersonalization and achieved significantly higher scores on the Athens Insomnia Scale. The determinants of burnout syndrome identified by the regression analysis were: sociodemographic factors (age, gender, and financial resources), the factors connected with the studying environment (year of studies and clinical and academic stressors), and emotional/mental/interpersonal factors (anxiety, depression, insomnia, and intensity of stress related to life situations). Conclusion The academic community should be encouraged to create a more supportive environment for students, which will ultimately prevent dropouts and increase the number of nursing professionals in the Polish healthcare system. We recommended carrying out regular screening tests for burnout, insomnia, anxiety, stress, and depression (e.g., once a year) among students. Depending on the results of the tests, implementation of interventions aiming at reducing the negative outcomes of burnout syndrome and promoting well-being and adaptive management mechanisms should be considered.